2012
DOI: 10.1515/bot-2011-0063
|View full text |Cite
|
Sign up to set email alerts
|

Delayed modifications in plant-water relations in the coastal marsh halophyte Spartina patens following sudden increases in soil salinity

Abstract: Little is known about how upper marsh plants (growing in freshwater) will respond physiologically to sudden increases in salinity. In this study, we used experimental microcosms to evaluate changes in plant-water relations in the halophyte Spartina patens following increases in soil salinity (salinity levels: 15, 30, and 45). There was a delay (by 3–5 weeks) in the lowering of leaf water potential (ψleaf), stomatal conductance (g), and tissue water content (θ) in plants subjected to salinities of 30–45. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 0 publications
3
13
0
1
Order By: Relevance
“…At both salinity concentrations, this change in leaf Ψs 100 (DΨs 100net ) was about 0.6 MPa (Table 1), indicating that the maximum reduction was achieved at 100 mM NaCl, and that this plant cannot reduce its osmotic potential beyond this external salt concentration. The present results are in line with those of Saltpeter et al (2012), who showed that low water availability together with the presence of salt in the environment causes active osmotic adjustment. Thus, osmotic adjustment is, perhaps, the main adaptive mechanism used by plants to limit the osmotic effects of salt stress (Saltpeter et al 2012;Flowers et al 2015).…”
Section: Water Parameterssupporting
confidence: 93%
See 3 more Smart Citations
“…At both salinity concentrations, this change in leaf Ψs 100 (DΨs 100net ) was about 0.6 MPa (Table 1), indicating that the maximum reduction was achieved at 100 mM NaCl, and that this plant cannot reduce its osmotic potential beyond this external salt concentration. The present results are in line with those of Saltpeter et al (2012), who showed that low water availability together with the presence of salt in the environment causes active osmotic adjustment. Thus, osmotic adjustment is, perhaps, the main adaptive mechanism used by plants to limit the osmotic effects of salt stress (Saltpeter et al 2012;Flowers et al 2015).…”
Section: Water Parameterssupporting
confidence: 93%
“…The present results are in line with those of Saltpeter et al . (), who showed that low water availability together with the presence of salt in the environment causes active osmotic adjustment. Thus, osmotic adjustment is, perhaps, the main adaptive mechanism used by plants to limit the osmotic effects of salt stress (Saltpeter et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned, several studies have shown strong associations between elevated environmental salinities and increased tissue rigidities ( Bolaños and Longstreth 1984 ; Salpeter et al 2012 ). These findings, in general, suggest that marine halophytes should have higher ɛ values compared with freshwater or terrestrial plant species.…”
Section: Introductionmentioning
confidence: 88%